Role of inter genic interactions in inheritance of Alternaria leaf blight resistance in inter and intraspecific crosses of Brassica carinata and Brassica juncea - Vinod Kumar; Vedna Kumari; PD Meena; Ashok Kumar (Journal of Oilseed Brassica, 2026)
The present study was carried out to study the genetics of inheritance of Alternaria blight resistance in rapeseed-mustard.Three crosses involving susceptible × moderately resistant genotypes viz., Jayanti × P(4)2b, Jayanti × EC-399300 and RCC-4 × EC-399300 were developed and evaluated. However, no concrete ratio could be fitted in F2 population as diseasereaction varied from moderate to high susceptibility and the available donor sources do not have high level of resistance.Therefore, six-parameter model was used to find out the gene effects for inheritance to Alternaria blight resistance using percent disease index (PDI) with square root transformation. Significance of A, C and D tests confirmed the presence ofepistasis. The study confirmed that at least more than one gene controls the inheritance of Alternaria blight resistance. Sixparametermodel showed significant estimates of additive [d], and non-additive [h] effects as well as all the three types ofepistasis viz., additive × additive [i], additive × dominance [j] and dominance × dominance [l]. The opposite signs of [h] and[l] indicated the presence of duplicate epistasis for the inheritance of Alternaria blight resistance.